2013
DOI: 10.1111/lam.12125
|View full text |Cite
|
Sign up to set email alerts
|

Regio-selectively reduced streptogramin A analogue, 5,6-dihydrovirginiamycin M1 exhibits improved potency against MRSA

Abstract: Significance and Impact of the Study: This study demonstrates the expanded applicability of the unique bio-hydrogenation activity of Streptomyces venezuelae towards macrocyclic lactone streptogramin A antibiotic and evaluates the enhanced anti-MRSA activity of the bioconverted analogue. The unique bio-catalytic feature of S. venezuelae could contribute to the biosynthesis and reconstruction of diverse therapeutic resources, particularly as a promising scaffold tailoring tool for creating antimicrobial agents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This changes in natural scaffold oligomycin and tilmicosin brought increased activity against S. cerevisiae and Bacillus subtilis respectively [133]. Similarly, macrocyclic lactone antibiotic streptogramin A namely 5, 6-dihydrovirginiamycin M1 was created by feeding virginiamycin M1 into a culture of recombinant S. venezuelae through the mechanism of bio-dehydrogenation catalysis [134]. The generated analog showed enhanced anti-MRSA activity compared to the parent compound.…”
Section: Microbial Biotransformation For Modification Of Antibioticsmentioning
confidence: 99%
“…This changes in natural scaffold oligomycin and tilmicosin brought increased activity against S. cerevisiae and Bacillus subtilis respectively [133]. Similarly, macrocyclic lactone antibiotic streptogramin A namely 5, 6-dihydrovirginiamycin M1 was created by feeding virginiamycin M1 into a culture of recombinant S. venezuelae through the mechanism of bio-dehydrogenation catalysis [134]. The generated analog showed enhanced anti-MRSA activity compared to the parent compound.…”
Section: Microbial Biotransformation For Modification Of Antibioticsmentioning
confidence: 99%
“…Consistent with this notion, the same region in this antibiotic molecule was previously identified as an avenue for the development of acetylation-resilient derivatives (9). As further validation of the importance of VatA Pro108 and Leu113 in the binding affinity for streptogramin A substrates, a recent study demonstrated that a derivative of virginiamycin M1 with a modification in this region (saturation of the C-28 -C-29 bond) that is expected to interact with these two residues showed altered binding affinity to VatA (25).…”
Section: Ct-domainmentioning
confidence: 99%